A Review of a Dissertation on the Topic of “Exploring the Effects of an Asynchronous Professional Development with the SAMR integration Model on High school Teachers’ Technology integration in the Classroom: An Action Research Study” - Kafle, Bharat (The Journal of Aadikavi, 2023)
The purpose of the review has critically analyzed the dissertation for the partial fulfillment of those who are interested in studying and makes fully activated along with participation for critical interpretation of different levels of various conceptions and components of the dissertation. Not only this, it helps to develop a critical lens and provide visions, building up wider perspectives on different burning issues but also increases the ontological and methodological interpretation regarding the side emic and etic perspectives of researchers in the field of research. In this review, I have used different relevant articles and document analysis methods in applying critical ways. I have critically analyzed all the contents of the dissertation and put them into five themes. They are introduction, Critical analysis of summary, context analysis, organization of writing, and conclusion. The basic elements and their evidence are included in it. I have examined the linking of the topic with its research questions with objectives, methodology, literature, discussions, and findings with a conclusion. In the review, the major problems appear to be inadequate technology for teacher training, lack of time for implementation of technology and professional development course, and improper utilization of the teachers. I have concluded that professional development is a wider topic that spans multiple disciplines for students helping them to improve via programming and computing devices and focusing on cycles of action and reflection.